Cloud-based negotiation for sustainable enterprise interoperability - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the 18th International ICE Conference on Engineering, Technology and Innovation (ICE 2012), 2012)
Competition and high ICT availability have driven enterprises to evolve by creating business nests where several enterprises gather their specialisations in the building of complete and fully-featured solutions. These business organisations are particularly important when regarding SMEs, and tend to be very dynamic with frequent inclusion of new enterprises. These enterprises thus need to develop dedicated business areas to handle the seeking for new partnerships, with its inherent need for interoperation, while maintaining the interoperability regarding the current ones. With a growing number of players and changes, this will rapidly lead to a non-interoperability scenario within the business network. This paper proposes a collaborative framework to support negotiations towards interoperability of organisations acting in a same industrial market, using a model-driven, cloud-based platform and services. The paper then specifies the application of the framework in a real-case scenario.